INFLUENCE OF MECHANICAL DEFORMATION ON PHOTOSENSITIVITY PROPERTIES OF THIN SEMICONDUCTOR FILMS (American Journal of Pedagogical and Educational Research, 2023)
The article presents arguments about the influence of mechanical deformation on the photosensitivity properties of thin semiconductor films.